Implementasi Teori Evaluasi Scriven (Sumatif – Formatif) dalam Pembelajaran PAI di SMPN 1 Sambit Ponorogo: Siti Kotijah, Suliana, Tirtania Aulia Putri, Tities Auliya, Vita Setiyana, Nurul Malikah - tirtania aulia putri99 (https://ejournal.insuriponorogo.ac.id/, 2024)
This study discusses the implementation of Scriven's evaluation theory, especially the formative and summative models, in learning Islamic Religious Education (PAI) at SMPN 1 Sambit. This study aims to explore the concept, application, benefits, and constraints of formative-summative evaluation in the context of the Merdeka Belajar curriculum. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results showed that formative evaluation is used to provide feedback on the learning process, while summative evaluation is used to assess student achievement at the end of the learning period. The implementation of these evaluations provides benefits in the form of improved learning quality and student understanding, although there are constraints such as limited time and facilities. This research suggests teacher training and the development of innovative evaluation strategies to overcome these constraints. These results are expected to contribute to the development of more effective and relevant PAI learning evaluations.